The Strategy to Improve the Profile of Pancasila Students in Early Childhood from Various National Backgrounds at CLC (Community Learning Centre) Kuala Lumpur, Malaysia - Sopiah, Cucu Sopiah; Shohehudin, Shohehudin; Nurhayati, Tati; Nurhasanah, Cucun (Universitas Al-Hikmah Indonesia, 2025)
This study aims to examine the implementation of the Pancasila Student Profile among Indonesian early childhood learners from diverse national backgrounds at Sanggar Belajar Sentul, a Community Learning Center (CLC) in Kuala Lumpur, Malaysia. The research employed a qualitative descriptive method through observation, interviews, and documentation. Findings revealed that the children’s knowledge of Indonesian national identity, including the President and Vice President’s names, the meaning of the national flag, and the Pancasila values, was very limited prior to the intervention. Through the application of culturally responsive strategies such as thematic learning, flag ceremonies, national song performances, and traditional games, gradual improvements were observed in the children’s understanding and recognition of Indonesian cultural symbols and values. The study highlights the importance of implementing contextual and creative educational programs in migrant learning environments to preserve national identity and recommends the development of structured, child-friendly modules for CLCs abroad